Vigilância alimentar e nutricional: quais são as barreiras enfrentadas por profissionais na atenção primária à saúde? - Oliveira, Andréia Silva de (2023)
The Food and Nutrition Surveillance (VAN) is defined as a strategy that allows knowledge about the food and nutrition conditions of the Brazilian population. However, recent studies suggest the existence of barriers associated with the organization of the VAN in Primary Health Care (APS), which may compromise its purpose. This study aimed to map the barriers for the organization of VAN by professionals in APS services in Brazil. A Scope Review was carried out according to the JBI method. The sources of information searched were LILACS/BVS-BIREME, BDENF/BVS/BIREME, BVS Public Health, Scopus/ELSEVIER, Web of Science Core Collection/Clarivate Analytics, CINAHL/EBSCO, ScienceDirect/ELSEVIER, CAB Abstract/CABI, Embase (Elsevier) and gray literature (dissertations and theses from Capes) with a time filter (2008 to 2021). Quantitative and qualitative observational primary studies, opinion and case studies and experience reports published in any language were included. Barriers relating to all stages of the Care Management and Production Cycle were mapped, as well as inherent to the resources needed to carry out the Cycle. Publications focused mainly on barriers related to the VAN data collection and recording phases, and human and material/physical resources. Barriers related to the VAN data collection and recording phases, as well as to human and material/physical resources, should be the subject of systematic literature reviews, so that inherent recommendations can be produced. The evaluation and action phases, in addition to financial resources, represent gaps in the literature that still need to be answered.